A Sociolinguistic Description of Language in Chimamanda Adichie’s Purple Hibiscus - Olaluwoye, Layo Esther (NIU Journal of Humanities, 2020)
This study is a sociolinguistic description of language in Chimamanda Adichie’s Purple Hibiscus . Through language, writers explore and extend the frontiers of knowledge. The use of English in Chimamanda Adichie’s Purple Hibiscus reflect adequately English in a second language environment; Adichie bends the English to her will, and sometimes change its structure to suit the Nigerian environment. William Labov’s variability theory which emphasizes the relationship of language use to social context forms the theoretical foundation of the study. The study reveals that Adichie’s Purple Hibiscus deploys the Igbo variety of the Nigerian English; this is evident through the choice of words, names of food, and proverbs in the bovel. The study also reflects the stratification of the society that Labov mentioned in the variability theory; variations in terms of sex, social status, education, etc. The study orients Nigerians and the international community about the variation in Nigeria’s linguistic culture.